Design of Service Oriented Architecture for an IoT Healthcare Management System - G. Hosary, Amira; Emran, Ahmed; El-Saghir, Basel (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
Healthcare services maturities are increasing dramatically over the last decade towards better patient anomaly detection, early diagnosis, and more accuracy in manipulation. The applications of IoT in healthcare are becoming more popular day after day with a good focus on the autonomy of detection and decision-making of patient’s vital data during admission phases, which could enable an envisioned environment for the right decisions on time. This paper focuses on developing a framework of architecture, protocols, and algorithms for IoT Healthcare system aimed at increasing the efficiency of systems operation and enhancing the reachability of different types of devices in the same patient or across several patients. The proposed architecture ensures that each individual device is autonomous and can work independently with the surrounding environment. The study includes as well as proof of concept pilot with a-capability to measure the patient’s vital information on a non-invasive basis, such as the pulse sensor unit, room temperature, and the display out device. The concept is validated, proving that devices can communicate together optimally, reliably, intelligently and autonomously in the same patient or across patient categories according to the status of patients without human intrusion.